1990
DOI: 10.1002/j.1552-4604.1990.tb01865.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Behavior of Orally Administered Radiolabeled Erythromycin Pellets in Man as Determined by Gamma Scintigraphy

Abstract: The behavior of single 250-mg doses of a multiparticulate form of erythromycin base (ERYC(R)), each including five pellets radiolabeled with neutron-activated samarium-153, was observed by gamma scintigraphy in seven male subjects under fasting and nonfasting conditions. The residence time and locus of radiolabeled pellets within regions of the gastrointestinal tract were determined and were correlated with plasma concentrations of erythromycin at coincident time points. Administration of food 30 minutes postd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…In a previous paper by our group a similar transit trend was noted; the upper small intestine transit of an enteric coated tablet appeared faster with a pre-feed dose (30 min before food) than that taken after food or on an empty stomach but this was inconclusive since the dosage form was designed to disintegrate in the distal intestine and therefore no relationship could be drawn between the arrival of food and the total small intestinal transit time of the tablet (15). Stronger evidence of a food effect on intestinal transit was noted by Digenis et al (14) who administered enteric coated erythromycin pellets 30 min before food and measured a 50% decrease in bioavailability with this dosing regimen; this was attributed to a more rapid small intestinal transit of the dosage form. This study, however, was complicated by the fact that erythromycin is a prokinetic drug which stimulates gastric and duodenal motility (23).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In a previous paper by our group a similar transit trend was noted; the upper small intestine transit of an enteric coated tablet appeared faster with a pre-feed dose (30 min before food) than that taken after food or on an empty stomach but this was inconclusive since the dosage form was designed to disintegrate in the distal intestine and therefore no relationship could be drawn between the arrival of food and the total small intestinal transit time of the tablet (15). Stronger evidence of a food effect on intestinal transit was noted by Digenis et al (14) who administered enteric coated erythromycin pellets 30 min before food and measured a 50% decrease in bioavailability with this dosing regimen; this was attributed to a more rapid small intestinal transit of the dosage form. This study, however, was complicated by the fact that erythromycin is a prokinetic drug which stimulates gastric and duodenal motility (23).…”
Section: Discussionmentioning
confidence: 87%
“…Might the arrival of food in the stomach trigger physiological mechanisms in the small intestine which alter the transit of the dosage form? A limited number of previous studies have considered alternative feeding regimens with modified release dosage forms and have reported conflicting effects on transit (14)(15)(16). Here, a study was designed specifically to investigate the timing of food administration on small intestinal transit.…”
Section: Introductionmentioning
confidence: 99%
“…The scintigraphic images showed that in the pre-feed regimen, faster small intestinal transit resulted in disintegration of the enteric beads in the distal regions of the small intestine compared to fasting conditions where drug release occurred in the proximal small intestine. This acceleration may limit absorption of those drugs that are preferably absorbed in the upper gastrointestinal tract (Digenis et al, 1990). This pre-feed acceleration in small intestinal transit and propulsion of the dosage form was explored further by Fadda et al (2009), where gastric emptying of tablets occurred before the arrival of food to the stomach in 60% subjects and small intestinal transit time in those subjects was found to be significantly shorter (100 min) than that observed in the standard fasted (204 min) and fed regimen (210 min).…”
Section: Gastrointestinal Transit Of Dosage Formsmentioning
confidence: 98%
“…There are other scenarios to consider, for example, administration of a multiple-unit formulation 30 min before food (pre-feed regimen) resulted in faster gastric emptying compared to when no food was administered. This suggests that food intake lead to an increase in gastric motility and consequently to a faster gastric emptying (Digenis et al, 1990).…”
Section: Gastrointestinal Transit Of Dosage Formsmentioning
confidence: 99%
“…These problems can be overcome by the incorporation of a non-radioactive tracer with subsequent radiolabelling by neutron activation (Parr et al 1987;Digenis et al 1990;Hardy et al 1991a;Wilding et al 1992c). Two materials, samarium-152 oxide and erbium-170 oxide are commonly used as tracers.…”
Section: Example 2: Evaluation Of An Enteric-coated Naproxen Tablet Rmentioning
confidence: 99%